2012
DOI: 10.1111/j.1745-9125.2012.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sexual Assault in Correctional Facilities: A Blocked Opportunity Approach*

Abstract: We use data from the National Incident‐Based Reporting System (NIBRS) to examine the effects of age on the risk of sexual and physical assault in prisons and jails. Our evidence suggests that male inmates of all ages tend to sexually assault young men. The preference for the young is much stronger for sexual than for physical assault, which suggests that the young are sexually assaulted because of their sexual attractiveness rather than because of their vulnerability. We argue that the strong relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
2
8
1
Order By: Relevance
“…While younger age has been reported as a risk factor in U.S. and Australian-based research (Chonco, 1989;Felson et al, 2012;Heilpern, 1998;Morash et al, 2012;Steels & Goulding, 2009;Wolff et al, 2007), we found no statistical association in this study. It should be noted that age considered in our analysis referred to age when surveyed and not age of sexual coercion event.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…While younger age has been reported as a risk factor in U.S. and Australian-based research (Chonco, 1989;Felson et al, 2012;Heilpern, 1998;Morash et al, 2012;Steels & Goulding, 2009;Wolff et al, 2007), we found no statistical association in this study. It should be noted that age considered in our analysis referred to age when surveyed and not age of sexual coercion event.…”
Section: Discussioncontrasting
confidence: 91%
“…One previous U.S.-based study found younger age to be a risk factor for sexual coercion of prisoners committed by staff as opposed to other prisoners (Wolff et al, 2007). Other studies have examined "official" reports of sexual coercion and thus under-reporting is likely (Chonco, 1989;Felson et al, 2012). This was supported by our finding, reported elsewhere (Richters et al, 2012), that only 30% who had experienced sexual coercion reported it to a staff member.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…. Younger age (Chonco, 1989;Felson et al, 2012;Morash et al, 2012;Wolff et al, 2007) . Small physical stature (Chonco, 1989;Jenness et al, 2007;Man and Cronan, 2001;Morash et al, 2012;Tewksbury, 1989) .…”
Section: Sexual Activity and Sexual Violence In Prisonsmentioning
confidence: 99%
“…Although some of the characteristics that increase adult inmate risk of sexual victimization directly describe youth, such as younger age and small physical stature (Man & Cronan, 2001;Tewksbury, 1989), they have not been shown to be significant predictors of risk among youth in custody (Ahlin, 2018). Similarly, several lines of evidence suggest that being female (see Beck, Berzofsky, et al, 2013;Teasdale et al, 2016) and new to prison (Felson et al, 2012;Hensley et al, 2005;Man & Cronan, 2001;Morash et al, 2012) are predictors of sexual victimization among adult inmates. However, recent research failed to find a correlation between youths' gender and sexual victimization, suggesting equal risk among boys and girls.…”
Section: Literature Reviewmentioning
confidence: 99%